MORPHOLOGICAL AND BIOINFORMATICS STUDY FOR RADIX AURICULARIA SNAILS IN FRESHWATER IN BASRAH PROVINCE, IRAQ - Al-Asadi, S. A. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Radix auricularia (Lymnaea auricularia) snails are the main intermediate host of Fasciola gigantica in the middle and South of Iraq. Recently, some studies suggest these snails are not present in Iraq, in particular Basrah province. Thus, the current study was aimed to use the bioinformatics analysis in the determination of Radix sp. in Basrah and also aimed to identify morphological characteristics of this species in the AL-Sewaib river, Basrah. Four hundred R. auricularia snails were collected from the AL-Sewaib river during May 2018 to March 2019. The results of the bioinformatics analysis showed according to the mitochondrial cytochrome c oxidase subunit I, the presence of R. auricularia snails in Basrah province and these snails are more closely related to Iranian R. auricularia snails than those for European counties and Russia. This study also displayed the existence of the polymorphism phenomenon in R. auricularia snails collected from the AL-Sewaib river which there were six different forms (A, B, C, D, E and F). These forms had variations in the colour and form of shells along with a variation in the number of eggs (30-56) per an egg mass. In addition to this, these R. auricularia forms had variations in their distributions. Form E had the highest spread percentage (33%) followed by 17, 15, 14, 11 and 10% for forms B, D, C, A and F, respectively. These forms had also variations in their morphological characteristics. The largest form was the form D whereas the smallest form was the form B but other forms A, C, E and F were similar and had moderate sizes.Thus, the current study concludes the existence of R. auricularaia snails in Basrah as a representative city for the southern part of Iraq and also confirmed the presence of the polymorphism phenomenon in the members of R. auricularaia obtained from the AL-Sewaib river.